Acid dyes removal using low cost adsorbents. (11th May 2004) - Aydin, A.H.; Bulut, Y.; Yavuz, O.
Dyestuff production units and dyeing units have always had pressing need techniques that allow economical pre-treatment for colour in the effluent. The effectiveness of adsorption for dye removal from wastewaters has made it an ideal alternative to other expensive treatment options. Removal of acid green 25 and acid red 183 from aqueous solution by different adsorbent such as shells of almond and hazelnut, and poplar and walnut sawdust were investigated. Equilibrium isotherms have been determined and analysed using the Freundlich equations. Parameters of Freundlich isotherm have been determined using adsorption data. Capacities of adsorbent follow as walnut > poplar > almond > hazelnut for AG25 and almond > walnut > poplar > hazelnut for AR183, respectively.